Sex-Specific Outcomes After Transcatheter Aortic Valve Replacement: A Review of the Literature. Issue 2 (March 2018) - Azarbaijani, Yasameen; O'Callaghan, Kathryn; Sanders, William E.; Wu, Changfu; Laschinger, John; Marinac-Dabic, Danica; Strauss, David G.; Canos, Daniel A.; Zusterzeel, Robbert
Abstract : Transcatheter aortic valve replacement (TAVR) is a safe and effective therapy for aortic valve replacement in patients ineligible for or at high risk for surgery. However, outcomes after TAVR based on an individual's sex remain to be fully elucidated. We searched PUBMED and EMBASE using the keywords: "transcatheter aortic valve replacement, " "transcatheter aortic valve implantation, " "sex differences, " "gender, " "sex characteristics" and collected information on baseline features, procedural characteristics, and postprocedural outcomes in women. Inclusion/exclusion resulted in 23 publications. Women had less preexisting comorbidities than men. Most studies reported better survival in women (range of hazard ratio [95% CI] = 0.27 [0.09–0.84] to 0.91 [0.75–1.10]). At 30 days, women also had more vascular complications (6–20% vs 2–14%) and higher bleeding rates (10–44% vs 8–25%). Stroke rates were similar at 30 days (women, 1–7%; men, 1–5%). This literature review showed better survival in women than men after TAVR. However, women had more vascular complications and bleeding; stroke rates were similar. These findings may partly be explained by fewer baseline comorbidities in women. These results should be interpreted with caution as most measures only include unadjusted percentages.